A Novel Ourmia-Like Mycovirus Confers Hypovirulence-Associated Traits on Fusarium oxysporum - Zhao, Ying; Zhang, Yuanyan; Wan, Xinru; She, Yuanyuan; Li, Min; Xi, Huijun; Xie, Jiatao; Wen, Caiyi (Frontiers in Microbiology, 2020)
Fusarium wilt caused by Fusarium oxysporum f.sp. momordicae (FoM) is an important fungal disease that affects the production of bitter gourd. Hypovirulence-associated mycoviruses have great potential and application prospects for controlling the fungal disease. In this study, a novel ourmia-like virus, named F. oxysporum ourmia-like virus 1 (FoOuLV1), was isolated from FoM. The viral genome has a RNA of 2,712 nucleotides (nt) in length, and contains one open reading frame (ORF) that can be translated into RNA-dependent RNA polymerase (RdRp) using either standard or mitochondrial codons. There is also includes a FoOuLV1-associated RNA segment with 1,173 nt, having no sequence homology. Phylogenetic analysis showed that FoOuLV1 is a member of the genus Magoulivirus within the family Botourmiaviridae. The presence of FoOuLV1 was found associated with hypovirulence in FoM strain HuN8, and the virus and its hypovirulence trait could be transmitted horizontally both to other FoM strains and to other formae speciale strains of F. oxysporum. In addition, the FoOuLV1 mycovirus showed a good biological control effect against the bitter gourd Fusarium wilt in both pot and field experiments. To our knowledge, this study reveals the first description of a hypovirulence-associated ourmia-like mycovirus, which has the potential for use in important applications related to the biological control of Fusarium wilt.